Investigations of the turbulent thermo-fluid performance in a circular heat exchanger with a novel flow deflector-type baffle plate - Rahman, Md Atiqur; Dhiman, Sushil Kumar (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
An axial flow tubular heat exchanger has been experimentally investigated to augment the heat transfer rate with a novel swirl flow of air past the heated tubes. The novel design has been based on circular baffle plates provided with trapezoidal air deflectors of various inclination angles. The arrangement of tubes is kept the same throughout the experiment, in accordance with the longitudinal airflow direction. The tubes maintained a constant heat flux condition over the surface. Four deflectors with equal inclination angles were developed on each baffle plate, generating air swirl inside a circular duct carrying the heated tubes that increase air-side turbulence and, consequently, the surface heat transfer rate. The baffle plates were placed equidistant from each other at variable pitch ratios. The Reynolds number was kept in the range of 16000– 28000. The effect of pitch ratios and inclination angles on the thermo-fluid performance of the heat exchanger was studied. The investigations revealed an average improvement of 3.75 times in thermo-fluid performance for an exchanger with a deflector baffle plate with a baffle inclination angle of 50_ and a pitch ratio of 1.4 when compared to other inclination angles and pitch ratios